Two-wing clappers for micro-air vehicle - Liew, Wei Jian (2016)
An experimental study was conducted to assess the aerodynamic benefits of using ‘Clap-and-Fling’ flapping flight mechanics for the development of Micro-Aerial Vehicle (MAV). The overall flight performance in terms of thrust generation of the ‘Clap-and-Fling’ flight was compared between the two different type of root chord with the wings which is “flexible root chord and fixed root chord” respectively. The experimental results clearly revealed that the ‘Clap-and-Fling’ mechanics with flexible root chord provided significant aerodynamic benefits. The thrust/frequency ratio and the thrust/power ratio are higher for the passive wings. Furthermore in term of power consumption, flexible root chord have less power consumption compare to the fixed wing. The thrust/power to frequency ratio also suggested that the flexible root chord is more efficient overall.